Unemployment and financial development : evidence for OECD countries - Afonso, António (2021)
It has been argued that credit market frictions may contribute to high unemployment. Hence, we assess the relationship between financial development and the labor market in OECD countries during the period 1990–2020. Using a random effects model for a panel dataset, we conclude that an increase in market capitalization and in the volume of shares traded can significantly reduce the unemployment rate. Likewise, inflation and per capita GDP growth are found to have significantly affected the evolution of the unemployment rate during the period under study.